STUDY ON THE PRODUCTIVITY OF FISHING SHIPYARDS IN LAMPULO VILLAGE, BANDA ACEH - Thaib Rizwan; Dicho Alfalah; Rahmat Rizqi; Makwiyah A. Chaliluddin; Ilham Zulfahmi; Husaini (Jurnal Maritim Malahayati, 2023)
Banda Aceh City is a city in Aceh located at the end of Aceh Province. The vast sea area makes the waters of Aceh Province have great potential in the marine and fisheries sector, one of which is in the waters of Lampulo, Aceh Province. The shipyard located in Lampulo Village is active in serving repair and maintenance activities for fishing vessels, both fiber and wooden vessels. Research on productivity studies of shipyards in Lampulo Village, Banda Aceh was carried out for three months from December 2021 to February 2022. This study aims to examine productivity levels and factors that affect productivity at shipyards in Lampulo Village, Banda Aceh. The method used in this research is a survey by direct observation by making direct observations in the field, data analysis is carried out using the objective matrix (omax) method. The results showed that the productivity level of shipyards was 49.00%, with the factors that affect productivity, namely the number of absent employees with an importance weighting of 30%, the use of labor with an interest weight of 21%, effective working hours with an interest weight of 21. %, the use of machines with a weight of importance of 14% and actual working hours with a weight of importance of 14%.